Response bias reveals the role of interhemispheric inhibitory networks in movement preparation and execution. (28th January 2022) - Puri, Rohan; Hinder, Mark R.
Abstract: Human movement is influenced by various cognitive processes, such as bias, that dynamically shape competing movement representations. However, the neurophysiological mechanisms underlying the effects of bias on movement selection across the lifespan remains poorly understood. Healthy young ( n = 21) and older ( n = 20) adults completed a choice reaction-time task necessitating left- or right-hand responses to imperative stimuli (IS). Response bias was manipulated via a cue that informed participants a particular response was 70% likely (i.e., the IS was either congruent, or incongruent, with the cue); biasing was either fixed for blocks of trials (block-wise bias) or varied from trial-to-trial (trial-wise bias). As well as assessing the behavioural manifestations of bias, we used transcranial magnetic stimulation to determine changes in corticospinal excitability (CSE) and short- and long-interval interhemispheric inhibition (SIHI, LIHI) during movement preparation and execution. Participants responded more quickly, and accurately, in congruent compared to incongruent trials. CSE decreases occurred in both hands following the cue, consistent with the 'inhibition for impulse control' hypothesis of preparatory inhibition. In contrast, IHI modulations occurred in a hand-specific manner. Greater SIHI was observed during movement preparation in the hand biased away from, compared to the hand biased towards, the cue; furthermore, greater SIHI was observed during movement execution in the hand biased towards the cue when it was not required to respond (i.e., incongruent trial) compared to when it was required to respond (congruent trial). Additionally, during the movement preparation period, the LIHI ratio of the hand biased towards, compared to the hand biased away from, the cue was greatest when the cue varied trial-by-trial. Overall, the IHI results provide support for the 'inhibition for competition resolution' hypothesis, with hand specific modulation of inhibition during movement preparation and execution. Highlights: TMS assessed corticospinal excitability and inhibitory changes to response bias. Reduced excitability, regardless of bias direction, during response preparation. Hand specific increases in short- and long-interval interhemispheric inhibition. Corticospinal excitability reductions subserve 'impulse control' during preparation. A greater degree of short-IHI reflects 'inhibition for competition resolution'.